The Role of PDE in Transonic Aerodynamics and Morphing Wing Design : A Systematic Literature Review - Akhsan, Hamdi; Vania, Amanda Asti; Ermalia, Widia; Anggelina, Zanne (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
Fluid dynamics and aerodynamic design of aircraft wings play a crucial role in improving flight efficiency, especially in the transonic regime. This research aims to analyze the application of partial differential equations (PDE) in aircraft design optimization and explore technical solutions to challenges that arise in Computational Fluid Dynamics (CFD). Our research method is Literature Review (SLR) using systematic steps such as database search, screening and thematic analysis based on references from recent scientific journals from 2020 to present (2025) through ScienceDirect, Google Scholar, arXiv,MDPI, DOAJ dan Academia . An initial search yielded 234,939 journals on PDEs, but after selection, 36 journals met the inclusion criteria and were thematically analyzed. The main findings show that the Navier-Stokes, Continuity, and Bernouli Equations are the cornerstones in understanding the fluid flow behavior around an Aircraft wing. Advances in CFD technology have led to innovations, such as the application of morphing wings and winglets, which can improve aerodynamic efficiency and reduce fuel consumption. However, challenges such as CFD solver robustness, design complexity with many variables, and geometry constraints are still an obstacle in aerodynamic optimization. It can be concluded that utilizing PDE in CFD contributes significantly to the development of higher efficiency aircraft and supports design innovations that are more adaptive to modern aerodynamic demands, especially in the transonic regime.